Empirical moral psychology - Tuber (Unisinos), Edgard Charles (Controvérsia (UNISINOS) - ISSN 1808-5253, 2015)
Review GREENE, Joshua. Moral tribes: emotion, reason, and the gap between us and them. New York: Penguin Press, 2013. 432p.